Shisha related burns: A paediatric case series. Issue 3 (July 2021) - Diab, Jason; Jacques, Madeleine; Vandervord, John; Holland, Andrew J.A.
Highlights: Shisha smoking commonly occurs in the home setting with family where burn injuries tend to occur. Shisha smoking amongst the community reflects lax attitudes of smoke inhalation around family and children, and the potential for burn injury. Shisha related burns were commonly mid dermal or full thickness injuries with a mean age of 4.9 years. Hand injuries were the most common site of injury. Abstract: Introduction: The majority of burn injuries in the paediatric age group occur in the home environment and are preventable. Water pipe smoking, commonly known as shisha, is an old practice of tobacco smoking dating from the 16th century with the use of hot coals and water in social gatherings at homes or cafes. The increasing use of shisha worldwide in youth raises public health concerns regarding its detrimental health effects and potential for serious thermal injury. Our aim is to identify and classify epidemiological trends of shisha related burns in the paediatric age group across New South Wales and the Australian Capital Territory. Methods: A retrospective review from January 2009 – December 2019 at The Children's Hospital at Westmead Burns Unit. All burn injuries of age less than 16 years that attended or were referred to the unit were included in this study. Results: There were 10 patients who presented with a shisha related burn injury. There was an equal distribution of males to females with all burns occurring in the home or a park. The most common types of injury were a full thickness or mid-dermal burns respectively, three of which required split thickness skin grafting. Conclusions: Shisha smoking is part of many cultures that has many potential burn hazards to children and family. Educational awareness targeted to shisha users can bring a better understanding about its potential for burn injury in children.